State’s responsibility for violations of international law by it’s nationals - Rozlinda Mohamed Fadzil, (Fakulti Undang - Undang, 2001)

(untitled)
This article shall attempt to put forth the theory in international law regarding state responsibility, its nature and requirements in determining the relationship and liability of a State and its populace when violations of international law have been committed by the state’s citizens. The theory of fault, an essential backbone to state responsibility, shall also be analysed. The equally important principles of holding out and reparations shall also be briefly considered. The article shall also reflect succinctly on the present laws, with regards to terrorism, under the sub-heating of Acts of Private Individuals